Lactate levels: A reliable tool to predict mortality in acute type A aortic dissections?. Issue 5 (16th February 2022) - Shetty, Varun; Shales, Sufina; Narayan, Pradeep
Abstract: Lactate levels are surrogate markers of malperfusion in patients presenting with type A aortic dissections. Lactate measurement is simple, easy to perform, universally available, and thus can be an important tool for predicting mortality. However, the discriminatory power varies between studies and no cut‐off point has been defined that can determine outcomes in the most reliable fashion. The risk prediction based on lactate levels can be improved when combined with other clinical and laboratory prognostic factors. Further studies with a much larger sample size, need to be carried out using serial measurements at well‐defined time points to try and identify a cut‐off value. The addition of lactate values to existing risk prediction scores or developing a new score based on it should be the subject of future research.